Superior Supercapacitive Performance in Porous Nanocarbons - Ali, Gomaa A. M.; Shoriya Aruni, Abdul Manaf; Divyashree, A; K. F., Chong; Hegde, Gurumurthy (Elsevier, 2016)
Porous nanocarbons with average particle size 20–40 nm were developed using biowaste oil palm leaves as a precursor. Simple pyrolysis was carried out at 700 °C under nitrogen atmosphere. Obtained porous nanocarbons showed excellent porous nature along with spherical shape. Symmetric supercapacitor fabricated from porous nanocarbons showed superior supercapacitance performance where high specific capacitance of 368 F/g at 0.06 A/g in 5 M KOH were reported. It also exhibited high stability (96% over 1700 cycles) and energy density of 13 Wh/kg. Low resistance values were obtained by fitting the impedance spectra, thus indicating the availability of these materials as supercapacitors electrode. The presented method is cost effective and also in line with waste to wealth approach.